Indignity of Nazi data: reflections on the utilization of illicit research - Farahani, Iman (Springer Nature, 2025)
Human rights may feel self-apparent to us, but less than 80 years ago, one of the most advanced countries at the time acted based on an utterly contrary ideology. The view of social Darwinism that abandoned the idea of the intrinsic value of human lives instead argued that oppression of the inferior is not only inevitable but desirable. One of the many catastrophic outcomes is the medical data obtained from inhuman experiments at concentration camps. Ethical uncertainty over whether the resulting insights should be a part of the medical literature provides a chance to consider the seemingly irreplaceable social construct of human dignity. Would any medical benefit justify the utilization of this illicit data? Would utilization even qualify as an insult to the dignity of the exploited subjects, or is this a question about intersubjective meaning? This work discusses the wisdom in blind adherence to human dignity, the possibility of retrospective insults, moral complicity, contrary viewpoints, and possible resolutions.